Diskectomy during Pregnancy: Case Report and Review of the Literature - Kanas, Michel (Global Spine J, 2014)
Study Design Case report. Objective The purpose of this report is to discuss the management of a disk herniation during pregnancy and the indication and particularities of surgery in this situation. Methods We describe a case of diskectomy performed in a 35-year-old woman at 18 weeks of gestation. After 4 weeks of trying to manage the disk herniation with rest and medications without success, the muscle strength of the L5 right root decreased to grade 4, and the patient was not responding to intravenous analgesia. After discussion with the patient and family, a decision was made to perform the diskectomy. Results After surgery, the patient's pain lessened, and the Lasegue test became negative. Two weeks after the procedure, the patient's muscle strength was normal. In the 40th week of pregnancy, the patient gave birth without any complications. Conclusion When necessary, diskectomy can be indicated and performed during pregnancy. However, appropriate precautions must be taken. Awareness of these precautions is important for the success of the procedure and for the well-being of the mother and the newborn.